MAP kinases p38 and JNK are activated by the steroid hormone 1α,25(OH)2-vitamin D3 in the C2C12 muscle cell line - Buitrago, Claudia Graciela (2006)
In chick skeletal muscle cell primary cultures, we previously demonstrated that 1α,25(OH)2-vitamin D3 [1α,25(OH) 2D3], the hormonally active form of vitamin D, increases the phosphorylation and activity of the extracellular signal-regulated mitogen-activated protein (MAP) kinase isoforms ERK1 and ERK2, their subsequent translocation to the nucleus and involvement in DNA synthesis stimulation. In this study, we show that other members of the MAP kinase superfamily are also activated by the hormone. Using the muscle cell line C2C12 we found that 1α,25(OH)2D3 within 1 min phosphorylates and increases the activity of p38 MAPK. The immediately upstream mitogen-activated protein kinase kinases 3/6 (MKK3/MKK6) were also phosphorylated by the hormone suggesting their participation in p38 activation. 1α,25(OH) 2D3 was able to dephosphorylate/activate the ubiquitous cytosolic tyrosine kinase c-Src in C2C12 cells and studies with specific inhibitors imply that Src participates in hormone induced-p38 activation. Of relevance, 1α,25(OH)2D3 induced in the C2C12 line the stimulation of mitogen-activated protein kinase activating protein kinase 2 (MAPKAP-kinase 2) and subsequent phosphorylation of heat shock protein 27 (HSP27) in a p38 kinase activation-dependent manner. Treatment with the p38 inhibitor, SB203580, blocked p38 phosphorylation caused by the hormone and inhibited the phosphorylation of its downstrean substrates. 1α,25(OH) 2D3 also promotes the phosphorylation of c-jun N-terminal protein kinases (JNK 1/2), the response is fast (0.5-1 min) and maximal phosphorylation of the enzyme is observed at physiological doses of 1α,25(OH)2D3 (1 nM). The relative contribution of ERK-1/2, p38, and JNK-1/2 and their interrelationships in hormonal regulation of muscle cell proliferation and differentiation remain to be established.